CaFÉ: A Sensitive, Low-Cost Filtration Method for Detecting Polioviruses and Other Enteroviruses in Residual Waters - Belgasmi, Hanen; Miles, Stacey Jeffries; Sayyad, Leanna; Wong, Kimberly; Harrington, Chelsea; Gerloff, Nancy; Coulliette-Salmond, Angela D; Guntapong, Ratigorn; Tacharoenmuang, Ratana; Ayutthaya, Apiradee Isarangkul Na; Apostol, Lea Necitas G.; Valencia, Ma.Anne-Lesley D.; et al. (Frontiers in Environmental Science, 2022)
Acute flaccid paralysis (AFP) surveillance has been used to identify polio cases and target vaccination campaigns since the inception of the Global Poliovirus Eradication Initiative (GPEI) in 1988. To date, only Afghanistan and Pakistan have failed to interrupt wild poliovirus transmission. Circulation of vaccine-derived polioviruses (VDPV) continues to be a problem in high-risk areas of the Eastern Mediterranean, African, and Southeast Asian regions. Environmental surveillance (ES) is an important adjunct to AFP surveillance, helping to identify circulating polioviruses in problematic areas. Stools from AFP cases and contacts (>200,000 specimens/year) and ES samples (>642 sites) are referred to 146 laboratories in the Global Polio Laboratory Network (GPLN) for testing. Although most World Health Organization ̶ ̶ supported laboratories use the two ̶ phase separation method due to its simplicity and effectiveness, alternative simple, widely available, and cost-effective methods are needed. The CAFÉ (Concentration and Filtration Elution) method was developed from existing filtration methods to handle any type of sewage or residual waters. At $10 ̶ 20 US per sample for consumable materials, CAFÉ is cost ̶ effective, and all equipment and reagents are readily available from markets and suppliers globally. The report describes the results from a parallel study of CAFÉ method with the standard two-phase separation method. The study was performed with samples collected from five countries ̶ (Guatemala, Haïti, Thailand, Papua New Guinea, and the Philippines), run in three laboratories– (USA, Thailand and in the Philippines) to account for regional and sample-to-sample variability. Samples from each site were divided into two 500 mL aliquots and processed by both methods, with no other additional concentration or manipulation. The results of 338 parallel-tested samples show that the CAFÉ method is more sensitive than the two-phase separation method for detection of non-polio enteroviruses (P-value < 0.0001) and performed as well as the two-phase separation method for polioviruses detection with no significant difference (. P-value > 0.05). The CAFÉ method is a robust, sensitive, and cost-effective method for isolating enteroviruses from residual waters.